2010
DOI: 10.1002/acp.1734
|View full text |Cite
|
Sign up to set email alerts
|

Perceived causes of everyday memory problems in a population-based sample aged 39-99

Abstract: There is usually a weak relation between memory complaints and laboratory memory performance, but few studies have investigated what people perceive as causes of their everyday memory problems. This study investigated prevalence, severity and perceived causes of memory problems in a population-based sample (N ¼ 361, age-range 39-99). 30.2 per cent of the participants reported memory complaints (at least moderate memory problems). Higher age was associated with more severe memory problems, but the age-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…This form of long-term memory displays the largest degree of age-related decline (Ronnlund et al, 2005;Vestergren and Nilsson, 2010). Older adults, for example, have more difficulty recalling what they had for breakfast than do younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…This form of long-term memory displays the largest degree of age-related decline (Ronnlund et al, 2005;Vestergren and Nilsson, 2010). Older adults, for example, have more difficulty recalling what they had for breakfast than do younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…Vestergren and Nilsson [35] showed that multitasking, concurrent stress, and one’s age (or aging) were commonly viewed as causes of everyday memory failures. Adams-Price and Gonzales [36] found that “absent-mindedness” – involving distractions, disruptions from routines, or forgetting to implement a strategy one typically relies on – was frequently involved in older adults’ everyday memory problems (e.g., forgetting to take medications) [see also 37].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies on the relation between cognitive complaints and cognitive functioning have been made on elderly [20,21,22,23,24,25,26,27,28,29,30,31], while population studies on non-elderly adults are few with mixed results [32,33,34,35,36]. This in addition to methodological issues regarding measures of cognitive functioning in these studies make it difficult to draw any clear conclusions.…”
Section: Introductionmentioning
confidence: 93%